Making sense of the 2016 water crisis in San Andres, a Colombian Caribbean Island - Velasquez, Carolina (Anais Brasileiros de Estudos Turísticos, 2019)
In October 2015, the Colombian Institute of Hydrology, Meteorology and Environmental Studies (IDEAM) declared that the El Niño phenomenon had reached severe conditions, and later, on July 13, 2016, reported that conditions had returned to normalcy. One of the affected areas was San Andres, a touristic drought-prone Colombian Caribbean island. On April 2, 2016, there were 11 road protests spread throughout the south-center of the island where the Raizales, an ethnic-minority group, and people from poor neighborhoods burned tires, blocked streets, and held up signs saying, “We need water.” That was the official beginning of the water crisis, which had by then affected 14,000 people. On April 15, the local government, for the first time in its history, declared a State of Public Calamity, attributing the causes of the lack of water to the El Niño phenomenon. The government established the El Niño phenomenon as the only trigger of the crisis, but the ways in which the community framed and understood the water crisis were overlooked. Acknowledging the importance of the community voice, this research analyzes the way people were affected and public officials made sense of the water crisis. Thirty-four semi-structured interviews were conducted in August, 2016 with a variety of stakeholders. The results show that officials were more inclined to frame the water crisis as a problem triggered mainly by technical and natural issues. On the community side, people framed the water crisis as a problem where social issues like justice predominated. This study helps to expose and understand the complexity of the San Andres water crisis and ultimately contributes to the prevention of repeated or more severe crises.